Pelatihan Digital Marketing, Branding, dan Manajemen Keuangan bagi UMKM Pasar Obor Klamana - Rendi Yudhistira Pattiasina; Ade Andriani Renouw; Philipus Sinay; Yanti Timisela; Edward Clan; Lili S. J. Sapari; Meyta Longkutoy; Andrei Maryen (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Micro, Small and Medium Enterprises in Pasar Obor, Sorong, play a vital economic role yet face challenges regarding conventional operations, weak branding, and mixed finances. This community service program aimed to enhance the competence of 40 MSMEs through training in digital marketing, branding, and financial management. Using a participatory approach, the methods included interactive lectures, AI utilization for marketing content, packaging innovation, and simple bookkeeping. Evaluation results demonstrated significant improvement in participant understanding, achieving an aggregate post-test score of 78.1 (Digital Marketing: 76.8; Branding: 85.5; Finance: 72.0). It is concluded that contextual mentoring effectively transforms MSME mindsets toward technology adaptation and professional governance. Consequently, support for free internet infrastructure and business legality is recommended to sustain these economic impacts.